New records of water mites of the genus Atractides Koch, 1837 (Acari: Hydrachnidia, Hygrobatidae) from South Africa, with descriptions of five new species - Pešić, Vladimir; Smit, Harry; Gerecke, Reinhard (Zootaxa, 2011)
New records of water mites of the genus Atractides Koch, 1837 (Acari: Hydrachnidia, Hygrobatidae) from South Africa are presented. Five species new to science, Atractides cooki, A. dracomontanus, A. meridianus, A. capensis and A. neoscutifer are described; a first description of the male is given for A. pulcher K. Viets, 1956 and A. assimilis K.O. Viets, 1964. A key to the species of Atractides from South Africa is presented.